Spektrum Ketahanan Galur Haploid Ganda Turunan IR64 dan Oryza rufipogon yang mengandung QTL Ketahanan terhadap Penyakit Blas (Pir) - Dwinita Wikan Utami; Alberta Dinar Ambarwati; Aniversari Apriana; Atmitri Sisharmini; Ida Hanarida; Didier Tharreau; Santosa Santosa (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2007)
Resistance Spectrum of Double Haploid Lines Derivedfrom IR64 and Wild Rice Species, Oryza rufipogonContained the Blast Resistance QTL (Pir). Dwinita W.Utami, A. Dinar Ambarwati, Aniversari Apriana, AtmitriSisharmini, Ida Hanarida, Didier Tharreau, and Santosa.This study was initiated to determine the spectrum resistanceof the candidate durable blast resistance variety containedthe QTL (quantitative trait locus), Pir1 and 2. This QTLwas mapped on chromosome 2 detected using the advancedbackcross population (BC5) from the wild rice speciesOryza rufipogon to IR64. Pir (1 and 2) also establishedon double haploid (DH) population derived from the selectedlines of BC2F3 population, progenies from the sameparents. The DH lines were developed to speed up the fixationprocess of the recessive alleles in the selected lines.Near isogenic lines with different blast resistance genes andcombination were used in this study comparing to the DHpopulation on their resistance spectrum using the knownavr gene isolates both on green house and field screening.The determination of the resistance spectrum will useful onthe prediction of durability of blast resistance gene in DHpopulation. The results of spectrum resistance test in greenhouse and field showed that Pir1and Pir2 segregated on 1 : 1proportion related with specific respond to blast avr genePH14 and CM28 resistance. Pir1 was identic to Pi33 or Pi25and Pir2 to Pitq5 on spectrum resistance.